The Concept of Uswah Hasanah and Its Implementation in Islamic Family Education - Wien Khakleri; Salami Mahmud; Miftah Jannah; Syatria Adymas Pranajaya (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This study examines uswah hasanah as a pedagogical model in Islamic family education and addresses a recurring gap in prior discussions that often emphasize exemplary conduct as a moral ideal without offering an operational framework that parents can apply in everyday family life. Using a descriptive qualitative approach through a literature review, this article synthesizes peer reviewed studies and scholarly sources published between 2016 and 2025 that discuss uswah hasanah, exemplary education, and Islamic family education. The analysis was conducted through close reading and thematic coding to identify recurring concepts, implementation mechanisms, and educational outcomes associated with exemplary education in the family context. The findings indicate that the family as madrasah al ula is a decisive setting for character formation because children internalize values primarily through repeated observation of parental conduct. The synthesis further shows that the implementation of uswah hasanah can be organized into five interrelated dimensions, namely tarbiyah bi al qudwah, tarbiyah bi al adat, tarbiyah bi al mau idzah, tarbiyah bi al mulaahadzah, and tarbiyah bi al uquubah, which together form a coherent sequence from modeling and habituation to guidance, supervision, and responsible discipline. This article contributes a structured conceptual framework that links Islamic educational thought with practical parental strategies for character formation in the home and provides a foundation for future empirical studies across diverse family settings.